Primary prevention activities of the diabetic foot and self-care activities in patients with type 2 diabetes in the Hospital II Clínica Geriátrica San Isidro Labrador, Essalud - Mesares Damiano, Gloria Rosa (2017)
Objectives: To identify which primary prevention of diabetic foot hits the nurse and what self-care activities performed by the patient with type 2 diabetes. Materials and Methods: The type of study is descriptive and cross-sectional data collection survey was applied to nurses and diabetic patients over 18 years. Results: The results show that 83.6% of nurses performed the assessment of the foot, provides education 90.9%. 72.7% provide foot self-care techniques. Recommended 92.7% quit smoking and 98.2% reported the importance of attending to his control. With regard to self-care practices performed by the patients, 46.4% have a moderate level of self-care, 69.6% check their feet, 42.9% did not check the inside of their shoes, 60% no apply moisturizers, 44.6% continues to add sugar to their drinks, 45.5% of overweight patients, including both sexes. Conclusions: Most of nurses take almost all activities of primary prevention of diabetic foot highlighting an important activity assessment of the foot. Furthermore, there is a regular practice of self-performed by the patient, especially in the daily observation of the foot.